Microtriatoma trinidadensis (Lent, 1951) (Hemiptera, Reduviidae, Triatominae): first record in the state of Amazonas, Brazil - Dos Santos Souza, Eder; Silva Monte, Gersonval Leandro; De Paiva, Vinícius Fernandes; Galvao, Cleber (Pensoft Publishers, 2019)
Microtriatoma trinidadensis (Lent, 1951), previously known from Venezuela, Colombia, Suriname, Peru, Bolivia, and the Brazilian states of Mato Grosso, Pará, and Tocantins, is reported for the first time in Amazonas state, Brazil. We found in the collection of the Instituto Nacional de Pesquisas da Amazônia an unidentified female specimen of Microtriatoma. The specimen was collected in April 2010, in dried straw and foliage of açai palm, Euterpe precatoria Mart., from Monte Sião, municipality of Codajás, Amazonas state.
Keywords: Chagas disease; New record; Triatomines